The Aging Process for Women in Leadership Positions: The Imminence of Symbolic Death and Rebirth - Cepellos, Vanessa; Tonelli, Maria José (Organizações & Sociedade, 2022)
This article explores how women in leadership positions experience and develop ways to deal with their aging process in organizations in Brazil. As women have reached these top positions relatively recently, studies on the careers of younger women still dominate the literature. For this reason, the literature on aging women who hold corporate leadership positions is still scarce. Based on empirical data obtained from 58 in-depth interviews based on grounded theory, this research showed that women experience their aging process as symbolic physical, social, and professional deaths and face an age glass ceiling due to their age. However, they also create new life stories based on a redefinition of work and/or a search for a new career, a phenomenon we call ‘symbolic rebirth.’ This paper proposes concepts related to how women see their aging process, uncovering the dynamics and implications of aging for women. There seems to be no room to aging in corporations, even for women in leadership positions. Despite the innumerable changes that have taken place in recent decades, this organizational space is still associated with the male gender, and ageism persists even for women who are in top-ranking executive positions in corporations.